Best practices - Florio, Gwen, 1955- (Florio, Gwen, 1955- Nora Best mystery., 2022)
Trying to start her life over, Nora Best takes a job as a "team leader" at a retreat for troubled teens. All seems perfect but for the recent death of a girl. It's framed as suicide, but as Nora learns more about how the retreat is run, she grows suspicious--and determined to find out the truth